Volume Change in Frontal Cholinergic Structures After Traumatic Brain Injury and Cognitive Outcome - Östberg, Anna; Ledig, Christian; Katila, Ari; Maanpää, Henna-Riikka; Posti, Jussi P.; Takala, Riikka; Tallus, Jussi; Glocker, Ben; Rueckert, Daniel; Tenovuo, Olli (Frontiers in Neurology, 2020)
The cholinergic nuclei in the basal forebrain innervate frontal cortical structures regulating attention. Our aim was to investigate if cognitive test results measuring attention relate to the longitudinal volume change of cholinergically innervated structures following traumatic brain injury (TBI). During the prospective, observational TBIcare project patients with all severities of TBI (n=114) and controls with acute orthopedic injuries (n=17) were recruited. Head MRI was obtained in both acute (mean 2 weeks post-injury) and late (mean 8 months) time points. T1-weighted 3D MR images were analyzed with an automatic segmentation method to evaluate longitudinal, structural brain volume change. The cognitive outcome was assessed with the Cambridge Neuropsychological Test Automated Battery (CANTAB). Analyzes included 16 frontal cortical structures, of which four showed a significant correlation between post-traumatic volume change and the CANTAB test results. The strongest correlation was found between the volume loss of the supplementary motor cortex and motor screening task results (R-sq 0.16, p<0.0001), where poorer test results correlated with greater atrophy. Of the measured sum structures, greater cortical grey matter atrophy rate showed a significant correlation with the poorer CANTAB test results. TBI caused volume loss of frontal cortical structures that are heavily innervated by cholinergic neurons is associated with neuropsychological test results measuring attention.